Microlicia morrensis (Melastomataceae): the third species in the genus endemic to Morro do Chapéu, Bahia, Brazil - Pacifico, Ricardo; Almeda, Frank (Phytotaxa, 2020)
A new species of Microlicia is described from the municipality of Morro do Chapéu, Bahia, Brazil. Microlicia morrensis is apparently related to M. petasensis and differs by its leaves that have a denser indumentum of eglandular trichomes, hypanthia densely covered with eglandular trichomes, calyx lobes triangular to widely triangular and lacking a stout eglandular trichome at the apex, petals rounded at the apex, and antepetalous stamens with appendages 4/5 to totally divided into two lobes. Photos of herbarium material and dried floral parts, a distribution map, notes on its conservation status, and an identification key to the species of Microlicieae from Morro do Chapéu are provided.